ANALISIS SANITASI DAN STRATEGI PENGENDALIAN LALAT DI PELABUHAN KAWASAN INDUSTRI DUMAI (KID) PELINTUNG - Abdi Candra; Usman M Tang; Elda Nazriati (Program Pascasarjana Universitas Riau, 2016)
This study aims to analyze and observe the condition of port sanitation with flies density. The results of pre-survey at canteen and dock of Dumai Industrial Estate port (DIE) Pelintung, show that poorly sanitary conditions thus leading to high density of flies. Besides, lack of attention and awareness of canteen and dock owner in maintain environmental sanitation. This study was using a survey method toward the conditions of harbor sanitary. Techniques of data retrieval were observation, questionnaires and interviews. Data analysis was quantitative and qualitative. The results obtained from this study was the sanitary condition of Dumai Industrial estate Port (DIE) Pelintung, not yet qualified healthy harbor, especially not waterthight sewage, not closed, not fluent canal, puddles, unclean bathroom/toilet, odor, inadequate in number not watertight landfills. Statistical test result showed that there was a strong correlation (r = 0.816) and significant (p = 0.007) between the sanitary conditions with the density of flies. Environmental sanitary condition of Dumai Industrial Estate Port (DIE) Pelintung was not ineligible, the density of flies in canteen was high and in dock was fair, there was a correlation between the port sanitary conditions with the density of flies and application of Integrated Vector Control (IVC) was not running well. The port sanitary conditions should to be improved, especially sewage, bathroom/toilet and bins to reduce the density of flies vector, and apply Integrated Vector Control (IVC).